Factors Affecting CSR Disclosure on Palm Oil Companies in Indonesia - Effendi, Asep (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The expansion of oil palm cultivation in Indonesia has begun to grow rapidly over the last few decades. Private and government companies play a role in the expansion of oil palm cultivation which currently has a high selling value in the national and global markets. However, the impact of the palm oil industry has a considerable risk both environmentally and socially. To reduce the risk of social conflict with local communities, oil palm companies have begun to increase their attention to Corporate Social Responsibility (CSR). Disclosure of Corporate Social Responsibility as an encouragement to increase public confidence in the achievement of efforts to improve and improve the environment around the company. The information provided must be transparent and accountable for its social activities so that disclosure of Corporate Social Responsibility (CSR) is important. This study aims to analyze the factors that influence the disclosure of CSR reports in 2017-2019. The method used in this research is descriptive quantitative with purposive random sampling technique, the number of samples is 7 companies that have stable profits and annual report records listed on the Indonesia Stock Exchange. This research uses the multiple linear regression analysis methods and t-test. The results showed that there was a significant influence between leverage ratios, public ownership, firm size (size), on the disclosure of social responsibility (CSRD). On the other hand, there is no positive and significant effect of the profitability ratio on the disclosure of social responsibility (CSRD).Â